The effectiveness of an educational program on health index in MI patients hospitalized in CCU ward - Reihane Askari; Ahmadreza Yazdannik; Iraj Shamsi (Journal of Education and Health Promotion)
Background: Acute myocardial infarction (MI), as a serious and fatal heart disease and an important medical emergency, imposes the large financial burden on the health and treatment systems of countries and the family economy. In the meantime, starting rehabilitation programs after acute myocardial infarction as soon as possible can minimize the unfortunate and irreparable side effects. Therefore, the present study was conducted with the aim of evaluating the effectiveness of an educational program on health index in the MI patients hospitalized in CCU ward. Materials and Methods: This study was conducted as a clinical trial on 60 patients with acute myocardial infarction referred to hospitals affiliated to Isfahan University of Medical Sciences in 2022. The intervention group (n = 30) and control group (n = 30) were divided randomly. The intervention group received a 6-step rehabilitation program and the control group received the routine care. Before, during and after the intervention, the physiological indexes of the patients (systolic and diastolic blood pressure, heart rate, arterial blood oxygen saturation) were monitored. Data were analyzed using the SPSS version 20 software and descriptive and inferential statistical methods. Result: Difference between changes in mean scores of the systolic and diastolic blood pressure, heart rate, arterial blood oxygen saturation between two groups, after the intervention compared to before the intervention was not statistically significant. Moreover, there was no significant difference, during the intervention compared to before the intervention and after the intervention (P > 0 05) but clinically significant improvement was observed. Conclusion: Early movement of a patient with acute myocardial infarction does not cause negative changes in the physiological indexes and hemodynamic stability of the patient. Therefore, the use of early movement program in the treatment and care plan of acute myocardial infarction patients is safe and possible and useful considering the complications of prolonged immobility.